2015
DOI: 10.14814/phy2.12342
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of female gender in programmed accelerated renal aging in the rat

Abstract: The aging kidney exhibits a progressive decline in glomerular filtration rate, accompanied by inflammatory and oxidative damage. We hypothesized that accelerated, age-related progression of renal injury is ovarian hormones-dependant. To address this we used an established model of developmentally programmed accelerated renal aging in the rat, superimposed by ovariectomy to assess interactions between ovarian hormones and the aging process. Under our experimental conditions, we found that kidney function worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
(64 reference statements)
2
20
0
Order By: Relevance
“…As highlighted above, numerous models of developmental programming report a sex difference in blood pressure (9, 24, 26, 27, 28) with onset of increased CV risk delayed in females (24, 25, 29, 30). Although the importance of endothelin ( ET-1 ) as a potential contributor to the pathogenesis of hypertension and increased CV risk following a fetal insult has undergone limited investigation, recent studies published in Hypertension indicate that the ET-1 system may contribute to sex differences in increased CV risk that has its origins in early life.…”
Section: Endothelin Sex Differences and Programmed Cardiovascular Riskmentioning
confidence: 97%
See 1 more Smart Citation
“…As highlighted above, numerous models of developmental programming report a sex difference in blood pressure (9, 24, 26, 27, 28) with onset of increased CV risk delayed in females (24, 25, 29, 30). Although the importance of endothelin ( ET-1 ) as a potential contributor to the pathogenesis of hypertension and increased CV risk following a fetal insult has undergone limited investigation, recent studies published in Hypertension indicate that the ET-1 system may contribute to sex differences in increased CV risk that has its origins in early life.…”
Section: Endothelin Sex Differences and Programmed Cardiovascular Riskmentioning
confidence: 97%
“…Yet, female offspring exposed to an insult during fetal life do not remain protected against an increase in blood pressure in later life (25, 29). Previous studies addressing the importance of the renal nerves and SNA in the developmental programming of hypertension involve studies performed in male offspring (10, 11, 17, 23).…”
Section: The Sympathetic Nervous System and The Developmental Programmentioning
confidence: 99%
“…This model which mimics chronic undernutrition in regions that suffer from extreme malnutrition in developing countries is useful for studying the mechanisms by which early growth patterns are related to adult cardiovascular disease. However, the developmental programming effects of a maternal low protein diet vary greatly due to differences in dietary components of the protein restricted diets [7778] and the method used for measurement of BP [67,7980]. Additionally, the severity of the restriction of protein in the maternal diet also results in sex-specific programming of CV risk [67].…”
Section: Introductionmentioning
confidence: 99%
“…Joles et al reported that, fetal exposure to low protein during gestation increased renal injury in the aging male kidney [81] (Figure 3). Yet, an additional study indicated that female offspring exposed to moderate maternal protein restriction during fetal life were protected against the accelerated development of renal injury [79]. Removal of the ovarian hormones accelerated age-related reductions in GFR and worsened albuminuria in female low protein offspring [79] (Figure 4) indicating that similar to the model of placental insufficiency, ovarian hormones played a protective role in the programming of chronic health in female offspring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation